Histological Differentiated/Undifferentiated Mixed Type Should Not Be Considered as a Non-Curative Factor of Endoscopic Resection for Patients With Early Gastric Cancer - Tang, Xiaolong; Zhang, Mengjun; He, Qingsi; Sun, Guorui; Wang, Chao; Gao, Peng; Qu, Hui (Frontiers in Oncology, 2020)
Background: Histological differentiated/undifferentiated mixed-type adenocarcinomas are frequently found in patients with early gastric cancer (EGC). Yet, it is unclear whether these mixed-type adenocarcinomas can be treated by endoscopic resection (ER) in EGC patients. Aims: To evaluate the lymph node metastasis (LNM) rate and long-term outcomes in mixed-type EGC patients and assess the feasibility of ER in these patients. Methods: Clinicopathological feathers, risk factors of LNM, and overall survival (OS) and progression-free survival (PFS) rates of EGC patients were analyzed according to different histological types. Results: Patients with mixed-type EGC had higher LNM rate than patients with non-mixed-type EGC (11.4% vs. 6.2%, P = 0.044). In the multivariate analysis, larger tumor diameter, presence of an ulcer, submucosal invasion, histological undifferentiated-type, histological mixed-type, and lymphovascular invasion resulted as independent risk factors for LNM in EGC patients (all P < 0.05). The LNM rate in mixed-type patients who met the Japanese ER criteria was 3.3%, including fulfilling the absolute criteria 0%. The 5-year OS and PFS rates in mixed-type patients were 94.59% and 91.47%, respectively. There was no statistical significance in the OS (P = 0.870) and PFS (P = 0.705) between mixed-type and non-mixed-type EGC patients fulfilling the Japanese ER criteria. Conclusion: Histological differentiated/undifferentiated mixed‑type in EGC patients meeting the Japanese absolute criteria for ER are associated with low risk of LNM and favorable prognosis, and thus should not be considered as a non-curative factor for ER.